AREA OF SCIENTIFIC AND PRACTICAL APPLICATION OF PROBLEM-BASED LEARNING - RASULOVA , DURDONA (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Abstract. The paper will then delve into the scientific and practical applications of problem-based learning. The scientific applications of problem-based learning will focus on its effectiveness in promoting learning outcomes in various fields of study, including medicine, engineering, and social sciences. The practical applications of problem-based learning will examine how it can be implemented in different educational settings, such as primary and secondary schools, higher education institutions, and vocational training centers. The paper highlights the significance of problem-based learning as a pedagogical approach that promotes critical thinking, problem-solving, and collaboration skills among learners. The paper will also provide recommendations for future research in the area of problem-based learning, including the need for more empirical studies to examine its effectiveness in different contexts and the development of guidelines and best practices for its implementation.